PENERAPAN DIRECT INSTRUCTION DISERTAI TEKNIK AKROSTIK TERHADAP HASIL BELAJAR MATERI KLASIFIKASI MAKHLUK HIDUP - Eka Maulida; Eka Ariyati; Reni Marlina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe purpose of this research was to know the effect of the direct instruction with acrostic technique to student learning outcomes in clasification material of living things in 7th Grade SMP Negeri 2 Semparuk. The form of this research was Quasi Eksperimental Design with Nonequivalent Control Group Design. The sample of this research included two classes which was VII D class as an expreriment class and VII E as a control class that using intac group technique.The data collection tool in this research was test questions. Based on the result of this analysis, the average score of the student learning outcomes using direct instruction with acrostic technique was 19,39, while student learning outcomes using conventional model was 16,47. Based on the calculation of N-Gain, the average of improvements in learning outcomes was 0,65, while in the control class was 0,52 where two classes have medium criteria. After t test is obtained tcount (4,63) > ttable (1,997) which mean that there was a difference of the student learning outcomes that using direct instruction with acrostic technique and conventional model in clasification material of living things. It showed that direct instruction with acrostic technique could increase the student learning outcomes in clasification material of living things in 7th Grade SMPN 2 Semparuk. Keywords : Acrostic, Direct Instuction, Learning Outcomes